Serum anti-Mullerian hormone level as a marker of polycystic ovarian syndrome in Iraqi women - Obeid, Shahad F.; Hassan, Bushra F.; Alhaidari, Taghreed K. (AL-Kindy College Medical Journal, 2015)
Background: Polycystic ovarian syndrome is one of the common gynaecological diseases encountered nowadays in the gynaecological clinic. Many criteria and diagnostic test had been evolved to be used with different classifications methods.Objectives: The present study aimed to measure the anti-mullerian hormone levels in serum of the women with Polycystic Ovary Syndrome and to test the possibility that if it can be used as a marker for diagnosis of polycystic ovary syndrome patients.Methods: A cross sectional study that had been conductedat Kamal AL-Samaraee Hospital, AL-Suwayrah Hospital andAl-Elwiya Maternity Teaching Hospital during the periodfrom July, 1st, 2013 – Jan. 1st, 2014. Where forty women withPolycystic ovarian syndrome (with mean body mass index of33.25±6.79kg/m2) were enrolled in the study group andbeing compared to apparently health women as a controlgroup that were matched for age and their (mean bodymass index was 27.63±3.51kg/m2). Clinical history,biochemical and hormonal analysis were determined forboth groups.Results: The mean serum of anti-mullerian hormone showed statically significant difference (P = 0.0001) in poly-Cystic ovarian syndrome patients compare to the controlgroup and when this hormone compared with other hormones that use for predicting the occurrence of PCOS as (LH , FSH , testosterone, prolactin and insulin), anti mullarian hormone showed the highest sensitivity and specificity as 82.10 % and 100 % respectively, with a cut off value of (>7.9) in Iraqi women.Conclusions: Anti - mullerian hormone could be the best marker in comparison with other hormones used for the diagnosis of PCOS.Keywords: Polycystic ovarian syndrome, anti-mullerian hormone, luteinizing hormone, follicular stimulating hormone.